ASYMPTOTIC SOLUTIONS OF MIXED PROBLEMS FOR ELASTIC STRIP AND WEDGE - Dmitry A. POZHARSKIY; Alexander A. MOLCHANOV (Advanced Engineering Research)
Asymptotic solutions are derived for two new theory elasticity problems with mixed boundary conditions. The first problem is about a shear crack in a strip for different types of boundary conditions on the outer faces of the strip. The second one is the contact problem for a three-dimensional wedge when a concentrated force is acting outside the contact domain on the wedge edge for sliding support on the other wedge face.